Exome sequencing identifies SUCO mutations in mesial temporal lobe epilepsy. (30th March 2015) - Sha, Zhiqiang; Sha, Longze; Li, Wenting; Dou, Wanchen; Shen, Yan; Wu, Liwen; Xu, Qi
Highlights: mRNA expression profiles divides the patients into two groups, severely and mildly affected patients, which are consistent with clinical phenotype. Exome sequencing results show that a novel mutant gene, SUCO, is shared by these severely affected patients. Knocking down SUCO expression in neurons impairs dendritic growth and development. SUCO colocalizes with rough endoplasmic reticulum in neurons. Abstract: Mesial temporal lobe epilepsy (mTLE) is the main type and most common medically intractable form of epilepsy. Severity of disease-based stratified samples may help identify new disease-associated mutant genes. We analyzed mRNA expression profiles from patient hippocampal tissue. Three of the seven patients had severe mTLE with generalized-onset convulsions and consciousness loss that occurred over many years. We found that compared with other groups, patients with severe mTLE were classified into a distinct group. Whole-exome sequencing and Sanger sequencing validation in all seven patients identified three novel SUN domain-containing ossification factor ( SUCO ) mutations in severely affected patients. Furthermore, SUCO knock down significantly reduced dendritic length in vitro . Our results indicate that mTLE defects may affect neuronal development, and suggest that neurons have abnormal development due to lack of SUCO, which may be a generalized-onset epilepsy-related gene.